Back Cover: Enhanced Functional Properties of Ti3C2Tx MXenes as Negative Electrodes in Sodium‐Ion Batteries by Chemical Tuning (Small Methods 9/2020). Issue 9 (10th September 2020) - Gentile, Antonio; Ferrara, Chiara; Tosoni, Sergio; Balordi, Marcella; Marchionna, Stefano; Cernuschi, Federico; Kim, Min‐Ho; Lee, Hyun‐Wook; Ruffo, Riccardo
Abstract : In article number 2000314, Riccardo Ruffo and co‐workers show that Ti3 AlC2 MAX phase is converted in two‐dimensional Ti3 C2 T x MXenes, whose electrochemical properties are enhanced by chemical modification. The bi‐dimensional Ti3 C2 T x MXenes are capable of delivering suitable capacity at high rate and in a very reversible way as negative electrode materials in sodium ion batteries.